2023
DOI: 10.3934/microbiol.2023013
|View full text |Cite
|
Sign up to set email alerts
|

Extended spectrum beta lactamase (ESBL)-producing <i>Escherichia coli</i> and <i>Klebsiella pneumoniae</i> in Indonesia and South East Asian countries: GLASS Data 2018

Abstract: <abstract> <p>Antimicrobial resistance is the rising global health issue that should not be ignored. This problem needs to be addressed and professionally handled since it is starting to threaten global health, which eventually could lead to disaster. Extended spectrum beta lactamase (ESBL)-producing bacteria were found threatening lives, since most antibiotics were found to not be effective in treating patients with infections caused by those bacteria. ESBL-producing <italic>Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…The bacteria that currently can cause health problems, especially in Indonesia, is Escherichia coli. Escherichia coli often causes infections in the urinary tract and bile duct and causes diarrhea (Sunarno et al, 2023). Diarrhea is the second cause of death in children under five years old and is the cause of death in about 760,000 children every year.…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria that currently can cause health problems, especially in Indonesia, is Escherichia coli. Escherichia coli often causes infections in the urinary tract and bile duct and causes diarrhea (Sunarno et al, 2023). Diarrhea is the second cause of death in children under five years old and is the cause of death in about 760,000 children every year.…”
Section: Introductionmentioning
confidence: 99%
“…The third-generation cephalosporins have been very widely used in Indonesia due to their cheap price, broad-spectrum, and clinical efficacy in the past few years [1]. This situation raises concerns about the emergence of multidrug-resistant organisms, in particular the extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-pE) in Indonesian hospitals as many studies reported that use of the third generation cephalosporines as a risk factor for the increase of ESBL-pE prevalence [2,3]. The Indonesia National Committee on Antimicrobial Resistance (KPRA) reported that the prevalence of blood stream infections caused by ESBL-pE in Indonesian hospitals increased from 40.0% on average in 2013 to 62.2% in 2016 [1].…”
Section: Introductionmentioning
confidence: 99%